Enhanced enzymatic saccharification of sorghum straw by effective delignification via combined pretreatment with alkali extraction and deep eutectic solvent soaking. (November 2021) - Wu, Mengjia; Gong, Lei; Ma, Cuiluan; He, Yu-Cai
Graphic abstract: Highlights: The types of HBA significantly affected ChCl-based DES pretreatment efficacy. Combination with dilute NaOH and ChCl:LAC was successfully used for treating SS. Combination pretreatment resulted in a much higher enzymatic digestibility. SS-hydrolysate was fermented to ethanol with a yield of 0.45 g ethanol/g glucose. Abstract: Hydrogen bond donor (HBD) in ChCl-based deep eutectic solvent (DESs) had significant influence on the Sorghum straw (SS) pretreatment. Lactic acid (LAC) was chosen as the appropriate HBD for preparing ChCl-based DES to pretreat Sorghum straw (SS). Furthermore, sequential pretreatment with dilute sodium hydroxide (0.75 wt%) for 1 h at 121 °C and ChCl:LAC soaking at 140 °C for 40 min was applied to pretreat SS for removing lignin (78.4%) and xylan (67.6%). Hydrolysis for 72 h, the reducing sugar yield reached 94.9%. Moreover, relationships of delignification and xylan removal with saccharification were explored after pretreatment. Finally, the fermentability of SS-hydrolysates was verified by bioethanol fermentation by S. cerevissiae with the yield of 0.45 g ethanol/g glucose. No significant inhibition was observed on ethanol fermentation. Obviously, establishment of high-efficient combination pretreatment with alkali extraction and ChCl:LAC soaking was successfully demonstrated for enhancing enzymatic saccharification of SS.